Baclofen facilitates the extinction of methamphetamine-induced conditioned place preference in rats - Voigt, Robin M. (2011)
The powerful, long-lasting association between the rewarding effects of a drug and contextual cues associated with drug administration can be studied using conditioned place preference (CPP). The GABA(B) receptor agonist baclofen facilitates the extinction of morphine-induced CPP in mice. The current study extended this work by determining if baclofen could enhance the extinction of methamphetamine (Meth) CPP. CPP was established using a six day conditioning protocol wherein Meth-pairings were alternated with saline-pairings. Rats were subsequently administered baclofen (2mg/kg i.p. or vehicle) immediately after each daily forced extinction session, which consisted of a saline injection immediately prior to being placed into the previously Meth- or saline-paired chamber. One extinction training cycle, consisted of six once-daily forced extinction sessions, mimicking the alternating procedure established during conditioning, followed by a test for preference (Ext test). CPP persisted for at least four extinction cycles in vehicle-treated rats. In contrast, CPP was inhibited following a single extinction training cycle. These data indicate that Meth-induced CPP was resistant to extinction, but extinction training was rendered effective when the training was combined with baclofen. These findings converge with the prior demonstration of baclofen facilitating the extinction of morphine-induced CPP indicating that GABA(B) receptor actions are independent of the primary (unconditioned) stimulus (i.e., the opiate or the stimulant) and likely reflect mechanisms engaged by extinction learning processes per se. Thus, baclofen administered in conjunction with extinction training may be of value for addiction therapy regardless of the class of drug being abused.